Maîtrise de l’eau et développement durable en Afrique de l’ouest : de la nécessité d’une coopération régionale autour des systèmes hydrologiques transfrontaliers - Frédéric Julien (VertigO)
In West Africa as elsewhere, human control over water resources is an essential element of sustainable development. In the region, this control means the exploitation of resources widely transboundary by nature and international water conflicts in West Africa can consequently be understood as obstacles to sustainable development. Conversely, achieving sustainable development in West Africa would demand a certain level of regional cooperation, but identifying the patterns of regional water conflict and cooperation could require a level of analysis above the typical river basin level. The concept of a “hydropolitical complex” is therefore proposed to this end.